EFFECT OF INSITU GREEN MANURING ON SOIL FERTILITY, GROWTH AND YIELD OF RICE UNDER ORGANIC FARMING - GANAPATHI; M.Y. ULLASA* (The Journal of Research ANGRAU, 2019)
The experiment was conducted to study the effect of insitu green manuring on soil fertility, growth and yield of rice under organic farming during kharif season for three consecutive years from 2012-13 to 2015-16.It was observed that the application of 100 kg Nequivalent FYM for preceding dhaincha (Sesbania aculeata) has produced higher green biomass yield (21.55 t ha-1) as compared to other green manuring crops with or without manuring. Incorporation of green manuring crop fertilized with 100 kg N equivalent FYM along with recommended dose of FYM (10 t ha-1) for succeeding rice crop has recorded significantly higher growth, yield attributes, grain (50.49 q ha-1) and straw yield (80.60 q ha-1). Also, the microbial population and final nutrient status of soil was found highest in the treatment which received 100 kg N equivalent FYM for dhaincha crop during sowing along with application of recommended dose of FYM for rice (10 t ha-1) during incorporation of dhaincha. The continuous application of FYM along with green manure for four consecutive years enhanced the soil chemical and biological properties.